Existence of positive solutions for the singular equation (φp(y'))' + g(t, y, y') = 0 - Haishen, Lu; O'Regan, D.; Chengkui Zhong (Нелінійні коливання, 2003)
Two theorems concerning the existence of positive solutions for the singular equation (φp(y'))'+g(t, y, y') = 0, y(0) = y(1) = 0, are presented. The results are obtained by using the nonlinear alternative of Leray – Schauder and the lower-upper solution method.